Ethics and Agriculture: A Teaching Perspective - Penelope L. Diebel (Journal of Agricultural and Resource Economics, 2008)
Ethics and agriculture is a complex debate, but one in which agricultural economics students must be prepared to participate. There are many links between economics and ethic or moral philosophy. Classroom teaching tends to focus on discussion of issues involving behavioral ethics and disregards the teaching of philosophical ethics and its application in agricultural economics. A discussion is presented regarding the ethical context we have inherited in agricultural economics. I offer some broad moral philosophy concepts and an argument for providing students with tools to develop a philosophical ethics perspective of agricultural economics.